Cognitive dysfunction and health-related quality of life among older Chinese - Pan, Chen-Wei; Wang, Xingzhi; Ma, Qinghua; Sun, Hong-Peng; Xu, Yong; Wang, Pei (Scientific reports, 2015)
We aimed to assess the association of cognitive dysfunction with health-related quality of life (HRQOL) among older adults in China. We analyzed community-based cross-sectional data of 5,557 Chinese individuals aged 60 years and above in the Weitang Geriatric Diseases Study. Cognitive dysfunction and HRQOL were assessed using the Abbreviated Mental Test (AMT) and the European Quality of Life-5 dimensions (EQ-5D), respectively. We estimated the impacts of cognitive dysfunction on the EQ-5D index and visual analogue scale (VAS) scores using linear regression models and the association between cognitive dysfunction and self-reported EQ-5D health problems using logistic regression models. The EQ-5D index and VAS scores were significantly lower for individuals with cognitive dysfunction than their counterparts. After controlling for covariates, the differences in EQ-5D index and VAS scores between individuals with and without cognitive dysfunction were −0.016 (95% confidence interval [CI]: −0.024, −0.008) and −3.4 (95% CI: −4.5, −2.4), respectively. Cognitive dysfunction was associated with reporting of problems in pain/discomfort (odds ration [OR]: 1.37; 95% CI: 1.12, 1.69) and anxiety/depression (OR: 2.13; 95% CI: 1.41, 3.23). The negative impact on HRQOL increased with the severity of cognitive dysfunction. The results indicate cognitive dysfunction was associated with worse HRQOL in older adults.